Recovering inorganic wastes - Vieira, M. T. (2003)
The aim of this work is to recover wastes by uniaxial pressing and injection moulding. A previous morphological, chemical and mineralogical identifications of different waste disposal batches guaranteed its reproducibility and revealed that in some cases they should be suitable to be treated by those conformation processes. Different tests regarding the chemical and structural evolution with temperature were performed with uniaxial pressed samples, which revealed that in all the cases there are formation of mullite and glassy phases. The presence of these phases contributes to a good physical and chemical behaviour of the fired parts. Moreover, the tests performed in a plastograph equipment to evaluate the rheological characteristics of different mixtures of waste powders with a commercial binder (function of temperature and applied load) show a good performance of these feedstocks to be injected. The typical thickness of injected products were less than 4.8 mm. After injection moulding or uniaxial pressing followed by sintering the final products present density and porosity values close to the theoretical ones. The Weibull modulus obtained with waste products is in the range of those of technical ceramics. These wastes have chemical and structural characteristics after firing that are interesting to the manufacturing of different ceramic products.